Usage of virtualization technologies in long-term preservation of integrity and accessibility of digital data - Milošević, Ivor (Array, 2011)
The concept of virtualization making a transition from expensive hardware systems over to the affordable software field, capabilities that modern virtual¬ization environments allow are becoming multidimensional and not many soft¬ware designers can allow their applications not to include some type of virtual¬ization system compatibility. Many applications allow virtualization systems to utilize them in such a manner that the performance is increased rather than hindered, and the level of collaboration among the users to be increased. Dis¬tribution of information, resources as well as entire operating environments can be very successfully and appropriately applied and used in systems for main¬taining authenticity and preserving long term usability of data.The authors an¬alyse requirements and suggest some initial high-level architectural solutions for the users of virtualization in the long term preservation process.